Hydrodynamic response analysis for a new semi-submersible vessel-shaped fish farm platform based on numerical simulation - Pang, Guoliang; Zhang, Song; Liu, Haiyang; Zhu, Shiyao; Yuan, Taiping; Li, Gen; Han, Xiangxi; Huang, Xiaohua (Frontiers in Marine Science, 2023)
Due to the polluted environment, limited resources and restricted room in the coastal aquaculture, the use of a large-scale fish farm platform aquaculture in deep sea areas is becoming more important for fish farming. However, the environment in deep sea is complex and harsh, which threatens the safety of fish farm platform due to the extreme weather. This work developed a new semi-submersible vessel-shape truss fish farm platform with single point mooring considering the different loading conditions. The dynamic performance of the platform was analyzed by numerical study. The numerical model of the fish farm platform was created at first. A physical model test was executed to verify the numerical model. It was found that the results from numerical model were in good agreement with the experimental results. Subsequently, the dynamic response of the platform under different wave conditions has been analyzed based on validated numerical model. The results showed that the new semi-submersible vessel-shape fish farm platform had good adaptability to extreme sea conditions. The experimental and numerical analysis of the structural behavior of the fish farm platform facilitates the design, analyses, and application of the deep-sea large fish farm platform.